A two-case series of entrapment of a ruptured balloon in the coronary artery: Avoidable complications and nonsurgical management - Wei-Ting Chang (Journal of the Formosan Medical Association, 2015)
The entrapment of a ruptured catheter balloon during percutaneous coronary intervention (PCI) is rare, but it can lead to life-threatening complications, such as myocardial infarction (MI) and lethal arrhythmias. Ruptured balloon entrapment usually occurs in either tortuous, calcified, or angulated coronary lesions without adequate balloon deflation. The avoidance of drastic balloon pull-out and the use of appropriate catheter-based retrieval techniques could prevent surgical intervention. Herein, we describe two cases of ruptured coronary balloon entrapment during emergency or elective PCI. We successfully removed the ruptured and entrapped balloons through nonsurgical techniques. Coronary interventionists should be aware of the possibility of balloon entrapment during complex coronary interventions; they should also become familiar with nonsurgical catheter-based methods for the retrieval of ruptured and entrapped balloons.